Community resilience, natural hazards, and climate change: Is the present a prologue to the future?. Issue 3 (26th May 2020) - Cutter, Susan L.
ABSTRACT: The nexus of natural hazards, climate change, and community resilience poses both conceptual and methodological challenges. One key consideration is the underlying notion of dynamic change or transformation in the systems that affect community resilience—social systems, natural systems, technological systems—and the degree to which the interdependencies influence who is resilient, to what, where, and to whom. The article examines community resilience from the broad perspective of affluent societies and illustrates the considerable variability in both the temporal and spatial nature of community resilience to natural hazards in the short term, and climate changes in the longer term, especially in more affluent societies. The author finds that, given the rapidity of environmental, social, economic, political, technological, and cultural changes, present circumstances and remedies may not be adequate predictors or precursors of future conditions. She concludes that the challenges associated with community resilience, natural hazards, and climate change require transformational thinking and action if achievements are to be made in terms of significant disaster risk reduction and any semblance of a sustainable future when extreme weather events will be the norm, not the exception.